Factors affecting the transition to adulthood of Korean young adults with spina bifida: a qualitative study - Eun Kyoung Choi; Jisu Park; Kyua Kim; Eunjeong Bae; Yoonhye Ji; Seung Hyeon Yang; Altantuya Chinbayar; Hyeseon Yun (BMC, 2023)
Abstract Background Transition to adulthood to live independently while self-managing health and daily life without parental help is crucial for young adults with chronic conditions. Despite its importance as a precursor to effectively managing lifelong conditions, little is known about the experiences of young adults with spina bifida (SB) in transition to adulthood in Asian countries. This study aimed to explore the experiences of Korean young adults with SB to identify the facilitators or barriers to the transition from adolescence to adulthood from their perspectives. Methods This study used a qualitative descriptive design. The data were collected in South Korea through three focus group interviews with 16 young adults with SB, aged 19-26, from August to November 2020. We conducted a qualitative content analysis using a conventional approach to identify the factors that facilitated and hindered the participants' transition to adulthood. Results Two themes emerged as facilitators and barriers to the transition to adulthood. a) Facilitators: understanding and acceptance of SB, acquiring self-management skills, parenting styles encouraging autonomy, parents' emotional support, school teachers' thoughtful consideration, and participation in self-help groups. b) Barriers: overprotective parenting style, experience of being bullied by peers, damaged self-concept, concealing one's chronic condition from others, and the lack of privacy in school restrooms. Conclusions Korean young adults with SB shared their experiences of struggling to properly manage their chronic conditions on their own, particularly concerning regular bladder emptying, during the transition from adolescence to adulthood. To facilitate the transition to adulthood, education on the SB and self-management for adolescents with SB and on parenting styles for their parents are important. To eliminate barriers to the transition to adulthood, improving negative perceptions of disability among students and teachers and making school restrooms CIC-friendly are needed.